Low-temperature high-water-content sludge curing agent as well as preparation method and application thereof

By using materials such as composite cement, ultrafine mineral blends and high-water-demand active powders, the problem of sludge curing in low-temperature environments in high-latitude coastal areas is solved, rapid curing and stable strength are achieved, and the requirements of rapid service of the project are met.

CN119912227AActive Publication Date: 2025-05-02CNBM ZHONGYAN TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510413544.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

In the low temperature environment of high-latitude coastal areas, how to make the silt with high moisture content reach hourly intensity in a short period of time and resist the erosion of seawater and meet the requirements of rapid service of the project remains a difficult problem.

Method used

Composite cement, ultrafine mineral blends and high-water-demand active powders are used as gelling materials, and high-water-demand active powders and enhancers are added, and water-reducing agents, water-absorbing resins, thickening agents, retarders and dispersants are added as compound admixtures to prepare a low-temperature high-water-content sludge curing agent. The curing agent has the characteristics of rapid curing, good dispersion resistance and green and low carbon under low temperature conditions.

Benefits of technology

It has achieved rapid curing and stable later-stage strength growth of high-water content silt under low temperature environments, has good anti-shrinkage ability, meets the requirements of rapid service of the project, and realizes the resource utilization of high-water seabed silt.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to a low-temperature type high-water-content sludge curing agent and a preparation method and application thereof. Composite cement and superfine mineral admixtures are adopted, and high-water-demand active powder and a reinforcing agent are matched to serve as main materials; a water reducing agent, water-absorbent resin, a thickening agent, a retarder and a dispersing agent are added to serve as compound additives, and the curing agent which can be used for curing high-water-content sludge and has the advantages of rapid curing, good dispersion resistance, environment friendliness and low carbon under the low-temperature condition is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a low-temperature high-water content sludge solidifying agent and a preparation method and application thereof. Background Art

[0002] In coastal areas, the middle and lower reaches of rivers, or near lakes, there is a large amount of silt and soft soil under the water surface.

[0003] The silt soft soil has extremely low strength, high compressibility and poor permeability, which results in low bearing capacity of the foundation in this area and slow strength growth.

[0004] Solidification treatment is a common method used both at home and abroad to realize the resource utilization of large amounts of dredged sludge.

[0005] In addition to the factors of the solidifying material itself, the initial moisture content of the silt also has an important influence on the final reinforcement effect of the solidified soil.

[0006] The prior art CN118993499A uses magnesium silicate, aluminum sulfate, polyferric sulfate, ammonium sulfate and quicklime as curing materials, which can effectively improve the early strength of the cured soil within 3-7 days and improve the construction efficiency. The moisture content of the cured soil is 120%-260%, the curing agent dosage is 8%-15%, and the 7d compressive strength can reach up to 900kPa.

[0007] In the prior art patent CN118239721A, ground slag and glass powder are used to modify marine sludge, the soil moisture content is 80%-90%, and the maximum compressive strength of the solidified body after 7 days can reach 4MPa.

[0008] The above-mentioned existing technologies can all handle silt with high water content. However, in high-latitude coastal areas, silt solidification construction is faced with low temperatures. Under the environmental conditions of high water content and low temperature, how to make the silt soil reach hourly strength and resist the erosion of seawater to meet the requirements of rapid service of the project still needs further research. Summary of the invention

[0009] In order to solve the problems existing in the prior art, the present invention provides a low-temperature high-water content sludge solidifying agent. Specifically, by adopting composite cement, ultrafine mineral admixtures, and combining high water demand active powder and reinforcing agent as main materials, adding water reducer, water absorbing resin, thickener, retarder and dispersant as compound admixtures, a solidifying agent for high-water content sludge solidification with fast solidification, good anti-dispersion, green and low carbon properties under low temperature conditions is prepared.

[0010] Specifically, the low-temperature high-water content sludge solidifying agent of the present invention is composed of the following raw materials in parts by weight: 10-15 parts of ordinary Portland cement, 25-30 parts of sulphoaluminate cement, 20-28 parts of ultrafine mineral admixtures, 20-30 parts of high water-demand active powder, 6-8 parts of reinforcing agent, 0.1-1 part of water reducing agent, 0.1-1 part of water-absorbing resin, 0.1-0.5 part of thickener, 0.1-1 part of retarder, and 0.1-2 parts of dispersant.

[0011] Preferably, the ultrafine mineral admixture is formed by mixing ultrafine fly ash, silica ash and mineral powder in a mass ratio of (1-2):(0.3-0.5):(2-3).

[0012] Preferably, the preparation process of the high water-requirement active powder is: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1: (0.5-0.8): (2-3), tableted, melted at high temperature, rapidly cooled, and ground to obtain fine powder; the fine powder and anhydrite are uniformly mixed in a mass ratio of (6.5-7): (3-4), and ultrafinely ground to obtain.

[0013] Preferably, the reinforcing agent is a mixture of CSH crystal nuclei, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of (0.5-5):(0.1-1):1.

[0014] The solidification of sludge with high water content is more difficult than that of ordinary sludge. First, the influence of high water content must be overcome, and the solidification of sludge particles must be achieved. To this end, the present invention adopts ordinary silicate cement and sulphoaluminate cement as composite cement, and adopts ultrafine mineral admixtures to improve the activity of cementitious materials, provide micro-filling effect to promote the discharge of water between sludge particles, and the present invention sintered high water-demand active powder at high temperature, and combined with a reinforcing agent to achieve low-temperature rapid solidification of high-water-content sludge.

[0015] The invention uses CaO, Al2O3 and SiO2 to prepare a high-water-demand active powder after high-temperature calcination and adding anhydrite. Compared with active ingredients such as cement and admixtures, the high-water-demand active powder has a higher water demand and good activity, and is more suitable for high-water-content sludge solidification. The reinforcing agent composed of CSH crystal nuclei, silicon nitride nano whiskers and methyldiethanolamine is used to improve the mechanical properties of the solidified body at low temperature.

[0016] Preferably, the thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and β-cyclodextrin in a mass ratio of (2-3):(1-2):(4-5).

[0017] The present invention adds part of the water-absorbing resin to absorb the moisture in the sludge. During the test, it is found that the use of the water-absorbing resin together with the thickener composed of polyaluminum sulfate, ammonium sulfate and β-cyclodextrin can ensure the mechanical properties of the solidified body, which is better than the single addition of water-absorbing resin or other types of thickeners. The cellulose ether thickener is easy to cause poor slurry molding effect and damage the mechanical properties.

[0018] Preferably, the strength grade of the ordinary Portland cement is ≥ 42.5. More preferably, the ordinary Portland cement is 52.5, wherein the C3S mineral content is not less than 70%.

[0019] Preferably, the strength grade of the sulphoaluminate cement is ≥52.5. More preferably, the sulphoaluminate cement is 72.5 and has a specific surface area of ​​350-400m 2 / kg.

[0020] Preferably, the fly ash D50 is 1-3 μm.

[0021] Preferably, the silica fume D50 is 1-2 μm.

[0022] Preferably, the mineral powder is S140 ultrafine mineral powder, and D50 is 3-5 μm.

[0023] Preferably, in the process for preparing the high water-requirement active powder, the high temperature melting temperature is 2000-2100° C., the heat preservation time is 10-15 min, and the ultrafine grinding adopts a jet mill.

[0024] Preferably, the specific surface area of ​​the high water-demand active powder is 900-1000cm 2 / g.

[0025] Preferably, the CSH crystal nuclei are prepared by a co-precipitation method.

[0026] Preferably, the silicon nitride nanowhisker has a particle size of less than 300 nm.

[0027] Preferably, the water reducer is a polycarboxylate water reducer.

[0028] Preferably, the particle size of the water-absorbing resin is 0.1-0.3 mm.

[0029] Preferably, the retarder is at least one of tartaric acid and boric acid.

[0030] Preferably, the dispersant is at least one of sodium hexametaphosphate, sodium polyacrylate and sodium pyrophosphate.

[0031] The present invention also relates to a method for preparing the low-temperature high-water content sludge solidifying agent, which specifically comprises the following steps: weighing various raw materials according to mass parts, mixing them evenly, and obtaining the solidifying agent.

[0032] The present invention also relates to the application of the low temperature high water content sludge solidifying agent in the solidification of high water content sludge.

[0033] The present invention has the following technical advantages: 1. The present invention uses composite cement, ultrafine mineral admixtures and high water-demanding active powder as cementitious materials, which can realize the solidification of high-water content sludge, and can effectively improve the early age strength and stable later strength growth of the solidified body under low temperature environment. 2. The high water-demanding active powder and enhancer of the present invention can improve the hydration process of the cementitious material system under low temperature environment and promote the low-temperature solidification of high-water content sludge. 3. The thickener composed of water-absorbing resin, polyaluminium sulfate, ammonium sulfate and β-cyclodextrin can fully absorb the free water in the sludge. 4. The curing agent of the present invention has fast setting and high strength, and the cured product has good anti-scouring ability. 5. The curing agent of the present invention has a simple preparation process, and after the sludge is solidified, it can be used for soft foundation treatment, road construction and other projects, thereby realizing the resource utilization of high-water-content seabed sludge. DETAILED DESCRIPTION

[0034] In order to characterize the technical effect of the present invention, a curing agent was prepared and mixed with seabed silt with a moisture content of 100%. The curing agent was added in an amount of 30% of the mass of the silt. Under a 5°C environment, the specimens were formed and unconfined compressive strength was tested in accordance with JTG E51-2009. The anti-scouring performance was tested using a 4m / s water flow. During the test, ordinary Portland cement was grade 52.5, sulphoaluminate cement was grade 72.5, and boric acid was used as a retarder.

[0035] Example 1 The curing agent is composed of the following raw materials in parts by weight: 12 parts of ordinary Portland cement, 27 parts of sulphoaluminate cement, 26 parts of ultrafine mineral admixture, 28 parts of high water-requiring active powder, 7 parts of reinforcing agent, 0.8 parts of polycarboxylic acid water reducer, 0.6 parts of water-absorbing resin, 0.5 parts of thickener, 0.6 parts of retarder, 1.5 parts of sodium hexametaphosphate, The ultrafine mineral admixture is made of ultrafine fly ash, silica ash and mineral powder in a mass ratio of 2:0.4:2. The preparation process of high water-requiring active powder is as follows: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1:0.6:3, pressed into tablets, melted at 1200℃ for 12 minutes, rapidly cooled, and ground into fine powder, and the fine powder and anhydrite are uniformly mixed in a mass ratio of 7:3, and ultra-finely ground to a specific surface area of ​​950cm 2 / g, that is, The reinforcing agent is a mixture of CSH crystal cores, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of 3:0.4:1. The thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and beta-cyclodextrin in a mass ratio of 2:2:4.

[0036] After testing, under an environment of 5°C, the unconfined compressive strength of the solidified body is 0.22 MPa after 3 hours, 0.85 MPa after 12 hours, 1.85 MPa after 1 day, and 5.76 MPa after 28 days. The solidified sludge does not disperse underwater and can withstand a water flow of 4 m / s.

[0037] Example 2 The curing agent is composed of the following raw materials in parts by weight: 15 parts of ordinary Portland cement, 26 parts of sulphoaluminate cement, 22 parts of ultrafine mineral admixture, 30 parts of high water-demand active powder, 6 parts of reinforcing agent, 0.8 parts of polycarboxylic acid water reducer, 1 part of water-absorbing resin, 0.2 parts of thickener, 0.7 parts of retarder, 1.6 parts of sodium hexametaphosphate, The ultrafine mineral admixture is made of ultrafine fly ash, silica ash and mineral powder in a mass ratio of 1:0.5:2.5. The preparation process of high water-requiring active powder is as follows: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1:0.6:3, pressed into tablets, melted at 1200℃ for 12 minutes, rapidly cooled, and ground into fine powder, and the fine powder and anhydrite are uniformly mixed in a mass ratio of 7:3, and ultra-finely ground to a specific surface area of ​​950cm 2 / g, that is, The reinforcing agent is a mixture of CSH crystal cores, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of 4:0.2:1. The thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and beta-cyclodextrin in a mass ratio of 3:1:5.

[0038] After testing, under an environment of 5°C, the unconfined compressive strength of the solidified body is 0.26 MPa after 3 hours, 0.91 MPa after 12 hours, 1.92 MPa after 1 day, and 5.90 MPa after 28 days. The solidified sludge does not disperse underwater and can withstand a water flow of 4 m / s.

[0039] Comparative Example 1 The curing agent is composed of the following raw materials in parts by weight: 15 parts of ordinary Portland cement, 26 parts of sulphoaluminate cement, 10 parts of silica fume, 12 parts of S95 grade mineral powder, 30 parts of high water demand active powder, 6 parts of reinforcing agent, 0.8 parts of polycarboxylic acid water reducer, 1 part of water absorbing resin, 0.2 parts of thickener, 0.7 parts of retarder, 1.6 parts of sodium hexametaphosphate, The preparation process of high water-requiring active powder is as follows: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1:0.6:3, pressed into tablets, melted at 1200℃ for 12 minutes, rapidly cooled, and ground into fine powder, and the fine powder and anhydrite are uniformly mixed in a mass ratio of 7:3, and ultra-finely ground to a specific surface area of ​​950cm 2 / g, that is, The reinforcing agent is a mixture of CSH crystal cores, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of 4:0.2:1. The thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and beta-cyclodextrin in a mass ratio of 3:1:5.

[0040] After testing, under an environment of 5°C, the unconfined compressive strength of the solidified body is 0.19 MPa after 3 hours, 0.77 MPa after 12 hours, 1.51 MPa after 1 day, and 4.36 MPa after 28 days. The solidified sludge does not disperse underwater and can withstand a water flow of 4 m / s.

[0041] Comparative Example 2 The curing agent is composed of the following raw materials in parts by weight: 15 parts of ordinary Portland cement, 26 parts of sulphoaluminate cement, 52 parts of ultrafine mineral admixture, 6 parts of reinforcing agent, 0.8 parts of polycarboxylic acid water reducer, 1 part of water-absorbing resin, 0.2 parts of thickener, 0.7 parts of retarder, 1.6 parts of sodium hexametaphosphate, The ultrafine mineral admixture is made of ultrafine fly ash, silica ash and mineral powder in a mass ratio of 1:0.5:2.5. The reinforcing agent is a mixture of CSH crystal cores, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of 4:0.2:1. The thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and beta-cyclodextrin in a mass ratio of 3:1:5.

[0042] After testing, it was found that under a 5°C environment, the solidified body had no strength after 3 hours, the unconfined compressive strength was 0.34 MPa after 12 hours, the unconfined compressive strength was 1.05 MPa after 1 day, and the unconfined compressive strength was 2.17 MPa after 28 days. The solidified sludge dispersed underwater.

[0043] Comparative Example 3 The curing agent is composed of the following raw materials in parts by weight: 15 parts of ordinary Portland cement, 26 parts of sulphoaluminate cement, 28 parts of ultrafine mineral admixture, 30 parts of high water-demand active powder, 0.8 parts of polycarboxylic acid water reducer, 1 part of water-absorbing resin, 0.2 parts of thickener, 0.7 parts of retarder, 1.6 parts of sodium hexametaphosphate, The ultrafine mineral admixture is made of ultrafine fly ash, silica ash and mineral powder in a mass ratio of 1:0.5:2.5. The preparation process of high water-requiring active powder is as follows: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1:0.6:3, pressed into tablets, melted at 1200℃ for 12 minutes, rapidly cooled, and ground into fine powder, and the fine powder and anhydrite are uniformly mixed in a mass ratio of 7:3, and ultra-finely ground to a specific surface area of ​​950cm 2 / g, that is, The thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and beta-cyclodextrin in a mass ratio of 3:1:5.

[0044] After testing, it was found that under a 5°C environment, the solidified body had no strength after 3 hours, the unconfined compressive strength was 0.60 MPa after 12 hours, the unconfined compressive strength was 1.36 MPa after 1 day, and the unconfined compressive strength was 4.05 MPa after 28 days. The solidified sludge dispersed underwater.

[0045] Comparative Example 4 The curing agent is composed of the following raw materials in parts by weight: 15 parts of ordinary Portland cement, 26 parts of sulphoaluminate cement, 22 parts of ultrafine mineral admixture, 31.2 parts of high water-requiring active powder, 6 parts of reinforcing agent, 0.8 parts of polycarboxylic acid water reducer, 0.7 parts of retarder, and 1.6 parts of sodium hexametaphosphate. The ultrafine mineral admixture is made of ultrafine fly ash, silica ash and mineral powder in a mass ratio of 1:0.5:2.5. The preparation process of high water-requiring active powder is as follows: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1:0.6:3, pressed into tablets, melted at 1200℃ for 12 minutes, rapidly cooled, and ground into fine powder, and the fine powder and anhydrite are uniformly mixed in a mass ratio of 7:3, and ultra-finely ground to a specific surface area of ​​950cm 2 / g, that is, The reinforcing agent is prepared by mixing CSH crystal nuclei, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of 4:0.2:1.

[0046] After testing, under an environment of 5°C, the unconfined compressive strength of the solidified body is 0.21 MPa after 3 hours, 0.80 MPa after 12 hours, 1.59 MPa after 1 day, and 4.95 MPa after 28 days. The solidified sludge is slightly dispersed underwater.

[0047] Comparative Example 5 The curing agent is composed of the following raw materials in parts by weight: 15 parts of ordinary Portland cement, 26 parts of sulphoaluminate cement, 22 parts of ultrafine mineral admixture, 30 parts of high water-demand active powder, 6 parts of reinforcing agent, 0.8 parts of polycarboxylic acid water reducer, 1 part of water-absorbing resin, 0.2 parts of hydroxypropyl methylcellulose ether, 0.7 parts of retarder, and 1.6 parts of sodium hexametaphosphate. The ultrafine mineral admixture is made of ultrafine fly ash, silica ash and mineral powder in a mass ratio of 1:0.5:2.5. The preparation process of high water-requiring active powder is as follows: CaO, Al2O3 and SiO2 are uniformly mixed in a mass ratio of 1:0.6:3, pressed into tablets, melted at 1200℃ for 12 minutes, rapidly cooled, and ground into fine powder, and the fine powder and anhydrite are uniformly mixed in a mass ratio of 7:3, and ultra-finely ground to a specific surface area of ​​950cm 2 / g, that is, The reinforcing agent is prepared by mixing CSH crystal nuclei, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of 4:0.2:1.

[0048] After testing, under an environment of 5°C, the unconfined compressive strength of the solidified body was 0.18 MPa after 3 hours, 0.63 MPa after 12 hours, 1.52 MPa after 1 day, and 4.77 MPa after 28 days. The underwater part of the solidified sludge was dispersed.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low temperature high moisture content sludge solidifying agent, characterized in that: The invention is composed of the following raw materials in parts by weight: 10-15 parts of ordinary Portland cement, 25-30 parts of sulphoaluminate cement, 20-28 parts of ultrafine mineral admixture, 20-30 parts of high water-requiring active powder, 6-8 parts of reinforcing agent, 0.1-1 part of water reducing agent, 0.1-1 part of water-absorbing resin, 0.1-0.5 part of thickener, 0.1-1 part of retarder, 0.1-2 parts of dispersant, The ultrafine mineral admixture is prepared by mixing ultrafine fly ash, silica ash and mineral powder in a mass ratio of (1-2):(0.3-0.5):(2-3). The high water-requiring active powder preparation process comprises: uniformly mixing CaO, Al2O3 and SiO2 in a mass ratio of 1: (0.5-0.8): (2-3), tableting, high temperature melting, rapid cooling, grinding to obtain fine powder, uniformly mixing the fine powder and anhydrite in a mass ratio of (6.5-7): (3-4), and ultrafine grinding to obtain, The reinforcing agent is prepared by mixing CSH crystal nuclei, silicon nitride nano whiskers and methyldiethanolamine in a mass ratio of (0.5-5):(0.1-1):

1. The thickener is prepared by mixing polyaluminium sulfate, ammonium sulfate and beta-cyclodextrin in a mass ratio of (2-3):(1-2):(4-5).

2. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: The strength grade of the ordinary Portland cement is ≥42.5, and the strength grade of the sulphoaluminate cement is ≥52.

5.

3. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: The fly ash has a D50 of 1-3 μm, the silica ash has a D50 of 1-2 μm, and the mineral powder is S140 ultrafine mineral powder, with a D50 of 3-5 μm.

4. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: In the high water-demand active powder preparation process, the high temperature melting temperature is 2000-2100° C., the heat preservation time is 10-15 minutes, and the ultrafine powder grinding adopts a jet mill.

5. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: The specific surface area of ​​the high water-demand active powder is 900-1000cm 2 / g.

6. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: The CSH crystal nucleus is prepared by a co-precipitation method, and the particle size of the silicon nitride nano whisker is less than 300 nm.

7. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the particle size of the water absorbing resin is 0.1-0.3 mm.

8. The low temperature high moisture content sludge solidifying agent according to claim 1, characterized in that: The retarder is at least one of tartaric acid and boric acid, and the dispersant is at least one of sodium hexametaphosphate, sodium polyacrylate and sodium pyrophosphate.

9. The method for preparing the low-temperature high-water content sludge solidifying agent according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: weighing various raw materials according to mass parts, and mixing them evenly to obtain the product.

10. Use of the low temperature high water content sludge solidifying agent according to any one of claims 1 to 8 in the solidification of high water content sludge.

Citation Information

Patent Citations

  • Quick-setting high-strength sludge curing agent and sludge curing process

    CN118405938A

  • High-water-content seabed sludge rapid curing agent and preparation method thereof

    CN118420300A

  • Slurry for ground improving work, improved ground formed by using the slurry, and dispersant for slurry for ground improving work

    JP2004256585A

  • Composition for tunnel reinforcement grouting

    KR101919838B1

  • Method for base or foundation reinforcement

    WO2009118376A1